2012
DOI: 10.7778/jpkm.2012.26.2.035
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Study on 121 Traffic Accident Child Patients

Abstract: ResultsIn the distribution of sex the ratio between boys and girls were similar, but regarding the age, 0~6 year-old group was more than that of 7~15 year-old group. In the traffic accident patterns, 87.6% of the entire children patients were injured by car crash. The highest type in the collision between cars was rear-ending impact. The most patients (48.8%) visited our hospital for oriental medical treatment in less than 3 days after the traffic accident. The number of the first visitors in the Oriental Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Because the patient's stress or psychological condition, immediately after a traffic accident, can affect the course of the symptoms, it was reported that other factors, such as psychological factors besides physical symptoms, can affect the prognosis 17) . In addition, as a characteristic group, pregnant women 18) and children 19) .…”
Section: Discussionmentioning
confidence: 99%
“…Because the patient's stress or psychological condition, immediately after a traffic accident, can affect the course of the symptoms, it was reported that other factors, such as psychological factors besides physical symptoms, can affect the prognosis 17) . In addition, as a characteristic group, pregnant women 18) and children 19) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, number of student death in ST crashes in Tehran, the capital of Iran, increased from fifteen in 2016 to 22 in 2018 [11]. The most prevalent injuries caused by ST crashes among children less than ten years and children aged 10-19 years are head trauma and lower extremity injuries, respectively [12]. Therefore, ST crashes are considered as serious threats to student health [13].…”
Section: Introductionmentioning
confidence: 99%
“…소아 교통사고 환자는 성인에 비해 증상 호소가 명확 하지 않으며 1) , 사고 이후 나타난 증상에 대한 자각 부 족으로 적절한 진단 및 치료를 받지 못하는 경우가 많 다 6) . 또한 수술을 요하지 않는 경미한 외상이나 검사 결과 특별한 이상 소견이 나타나지 않는 지속적인 통 증, 사고 후 나타난 야제(夜啼) 및 정서 불안에 대하여 현 양방 의료체계에서는 적절한 치료법이 없는 경우가 대부분이다 7) . 이와 같은 이유로 증상의 호전 및 후유증 예방을 위해 한방의료기관을 찾고 있는 소아 청소년 교 통사고 환자가 증가하고 있다.…”
unclassified